"The Marvelous Unknown of Another's Making": Aislinn Hunter's A Peepshow With Views of the Interior: Paratexts. Issue 2 (2nd April 2020) - wiesenthal, christine
Abstract: Aislinn Hunter is a Canadian writer whose work reveals a consistent fascination with visual and material culture. Although her books span multiple genres, this essay focuses on her most experimental (and, it is suggested, under-read) work to date, A Peepshow With Views of the Interior: Paratexts (2009). This essay offers an analysis of the book's intricate design, which is simultaneously paratextual and ekphrastic (the title of A Peepshow indicates one source of its inspiration in the seventeenth-century work of the highly experimental Dutch realist painter Samuel van Hoogstraten). The article begins with a consideration of the relevance of the paratextual form to A Peepshow 's concerns with the object world and a Heideggerian philosophy of things. The analysis then shifts to consider the relationship between paratext and ekphrasis as parallel arts of "framing, " especially as demonstrated by the example of van Hoogstraten's famous perspective box embedded within Hunter's own Peepshow . Finally, the essay seeks to extrapolate some broader implications from the encounter with this particular text, which both implicitly (in its very structure) and explicitly (in its critique of contemporary visual and verbal literacies) invites one to contemplate the effects of the medial transformation underway in the shift to more dispersed and nonlinear digitized textual forms.